(1/a-1/b)*((a+b)^2-a^2-b^2)/(a-b)^2)=
(1/a-1/b)*((a^2+2ab+b^2-a^2-b^2)/(a-b)^2)=
((1/a-1/b)*(2ab/(a-b)^2)=
((b-a)/ab)*(2ab/(a-b)^2)=
(-(a-b)/ab) *(2ab/(a-b)^2)=
-2/(а-b) =
2/(b-a)
ответ: 2/(b-a)
3) (a+b/a^2-ab-1/a):b/b-a
a(b/a-b-1):b/b-a (a-сокращаем)
(b/a-b-1):b/b
1) b-ab-a=b-ab
a
2) b-ab:b/b=ab(умноженная) b
3)0.5(умножен)7-2(умножен)7-2= -12,5
ответ: -12,5
C/sin 90=C (sin 90 градусов=1)
В прямоугольном треугольнике α+β=90
α=90-β
b/sin β =c b=c*sin β
a/sin α=c a=c*sin α=c*sin(90-β)=c*cos β
2. Из свойств прямоугольного треугольника
b/c=sin β
a/c=cos β
b=c*sin β
a=c*cos β
Выбирайте, что понравится